Phylogenetic appraisal of the genus Platoma (Nemastomatales, Rhodophyta), including life history and morphological observations on P. cyclocolpum from the Azores - Gabriel, Daniela (2007)
“[…]. The present study highlights a combination of vegetative and reproductive characters not described before for Platoma cyclocolpum (Fig. 1). Life history studies were conducted and the development of tetrasporophytes in culture is described. A phylogenetic tree inferred from chloroplast-encoded rbcL sequence analysis shows the position and the relationships of four Platoma species within the Schizymeniaceae (Schizymenia, Titanophora) and Nemastomataceae (Predaea, Nemastoma). An assessment of the diagnostic characteristics of Platoma is provided and comparisons made among the different species of the genus.” [Introduction].